Upaya Peningkatan Pemahaman Siswa Pada Materi Thaharah Melalui Metode Praktik di Lapangan: Efforts to Improve Students Understanding of Thaharah Material Through Practical Field Methods - Mariana, Mariana (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to improve students' understanding of the concept of thaharah through practical field methods. The research subjects were 29 seventh-grade students of MTs Tarbiyah Islamiyah Tanjung Agung during the second semester of the 2022/2023 academic year. The method used in this study was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included tests (pretest and posttest), observations, questionnaires, and documentation. The results indicated that the practical method significantly improved students' understanding of thaharah, evidenced by an increase in the average score from 58 (pretest) to 83 (posttest in Cycle II) and a rise in the number of students achieving the Minimum Competence Criteria (MCC) from 26.7% to 100%. Student engagement and participation also increased during the learning process. Thus, the practical field method is proven effective for Islamic jurisprudence (fiqh) education, especially for application-based topics such as thaharah.